Subclavian Artery Pseudoaneurysm Secondary to Accidental Stone Chip Injury and its Excision - SW Nagre (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
According to the literature data, post traumatic pseudoaneurysm is rare [1]. Most common site is common femoral artery, followed by radial and brachial artery but subclavian artery is very rare because trauma to it is rare. Incidence of complications associated with such pseudoaneurysm is estimated around 2-6% [2]. We present a case of the patient in whom pseudoaneurysm of left subclavian artery developed after five days of accidental stone chip injury and was successfully treated by surgical excision of pseudoaneurysm and removal of stone chip with direct closure of opening in subclavian artery.